Race in Rhinology Clinical Trials: A Decade of Disparity. (25th January 2021) - Spielman, Daniel B.; Liebowitz, Andi; Kelebeyev, Saveliy; Smith, Timothy L.; McKinney, Kibwei; Woodard, Troy; Safi, Chetan; Overdevest, Jonathan B.; Gudis, David A.
Abstract : Objective/Hypothesis: The aim of this study is to assess the ethnic and racial demographics of patients enrolled in prospective chronic rhinosinusitis (CRS) studies relative to the corresponding geographic demographics of the United States (U.S.) census data. Study Design: Systematic Review and Population analysis. Methods: A systematic review was performed to identify CRS clinical trials, conducted in the U.S. and published between 2010 and 2020 in which patients were prospectively enrolled. Pooled racial and ethnicity data were compared to national and corresponding regional census data. Results: Eighty‐three studies were included, comprising 12, 027 patients. 50.4% were male and the average age was 49.2 years. 8, 810 patients underwent a surgical procedure. Of the 12, 027 patients, 81.67% were identified as White, 5.35% as Black, 1.27% as Asian, 0.02% as Pacific Islander, 0.12% as American Indian, and 11.57% were classified as Other. The racial and ethnic composition of the pooled study population differs significantly from the national U.S. census data with the underrepresentation of each minority population ( P  ≤ .0002). Regional sub‐analyses yield variable results. In the Northeast and West, there was an underrepresentation of all minority populations. In the South and Midwest, Black enrollment was similar to the U.S. census data, while all other minorities were underrepresented. Conclusions: The racial and ethnic composition of patients enrolled in prospective CRS clinical trials differs significantly from the demographics of the U.S. population. The generalizability and external validity of findings derived from studies comprised of demographically mismatched populations has not been established. Future efforts to enroll more representative populations should be emphasized by the research community, funding bodies, and editorial boards. Level of Evidence: NA Laryngoscope, 131:1722–1728, 2021